MSCs can be a double-edged sword in tumorigenesis - Zhang, Lu; Xiang, Junyu; Zhang, Fang; Liu, Limei; Hu, Chongling (Frontiers in Oncology, 2022)
Mesenchymal stem cells (MSCs) have been used to treat various diseases including Alzheimer’s disease and cancer. In particular, the immunomodulatory function of MSCs plays a major role in cancer therapy using stem cells. However, MSCs exert promotive and inhibitory effects on cancer. The immunomodulatory effects of MSCs in the tumor microenvironment (TME) are ambiguous, which is the primary reason for the different outcomes of MSCs therapies for tumors. This review discusses the use of MSCs in cancer immunotherapy and their immunomodulatory mechanisms in cancers.